118k views
4 votes
Write the expression as a single natural logarithm;
3 ln 3 + 2 ln x

User JBoy
by
7.0k points

2 Answers

2 votes

ANSWER


3 ln(3) + 2ln(x) = ln(27 {x}^(2) )

EXPLANATION

The given logarithmic expression is


3 ln(3) + 2ln(x)

Recall and apply the power rule:


k \: ln(a) = ln( {a}^(k) )


3 ln(3) + 2ln(x) = ln( {3}^(3) ) + ln( {x}^(2) )


3 ln(3) + 2ln(x) = ln(27) + ln( {x}^(2) )

Apply the product rule:


ln(ab) = ln(a) + ln(b)


3 ln(3) + 2ln(x) = ln(27 {x}^(2) )

User Flory
by
5.2k points
3 votes

Answer:

ln (27 x²)

Explanation:

Given in the question an expression

3 ln 3 + 2 ln x

Step1

Apply power rule


mlnx=lnx^(m)

ln 3³ + ln x²

Step2

Apply multiplication rule


lnx + lny=ln(xy)

ln (3³ . x²)

3³ = 27

so

ln (27x²)

User Pankrat
by
6.1k points